Rosyjska baletnica - Steel, Danielle; Adamski, Pawel (Warszawa : Swiat Ksiazki, 2000)
Polish translation of "Granny Dan". The story of a Russian woman who emigrated to the US. Her granddaughter uncovers her life in Russia when she sifts through the mementos left behind after hehr grandmothers death.
Keywords: Grandmothers -- United States -- Fiction; Russian Americans -- Fiction; Soviet Union -- History -- Revolution, 1917-1921 -- Fiction